Studies on Aminobenzothiazole and Derivatives: Part-2. Synthesis of Intermediates -Substituted Phenylthiourea using Ammonium Thiocyanate: Studies on Aminobenzothiazole and Derivatives: Part-2. Synthesis of Intermediates -Substituted Phenylthiourea using Ammonium Thiocyanate - Patil, Dr. C. J. (International Journal of Pharmaceutical & Biological Archive, 2019)
The substituted phenylthiourea is used as intermediate in different reactions because they play an important role in synthesizing the heterocyclic compounds. These reactions involve the synthesis of an intermediate phenylammonium chloride which is converted to substituted thiourea using ammonium thiocyanate. The final product formed, substituted phenylthiourea has potential to use as an intermediate in the synthesis of a building block for the heterocyclic compound, 2-aminobenzothiazole.